(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In 21st-century American literature, the image of the hero has undergone a significant transformation. This article investigates the concept of modern heroism through the lens of two renowned novels—The Kite Runner by Khaled Hosseini and The Road by Cormac McCarthy. Unlike traditional heroes associated with physical bravery and public triumph, the protagonists in these works reflect a more introspective and ethically nuanced form of heroism. The study focuses on themes of guilt, emotional endurance, moral responsibility, and quiet sacrifice as new indicators of heroic identity. These novels reveal that modern heroism is not about overcoming enemies, but about confronting oneself and protecting vulnerable lives in the face of adversity.